Strategi Advokasi NGO dalam Konflik Pertanahan (Studi pada NGO WALHI Sum-Sel dan LBH Palembang dalam Advokasi Konflik Pertanahan Petani Rengas Versus PTPN VII Cinta Manis) - KHOLEK, ABDUL ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The title of this study Advocacy Strategy Non-Government Organization (NGO) in the Conflict of Land (Strategic Studies Advocacy NGO WALHI Sum- Sel and LBH Palembang in Farmer Land Conflicts Versus Rengas PTPN VII Cinta Manis, Ogan ILir in South Sumatra). The first of research problem focus, to see the dynamics of conflict, the secons to advocacy strategies undertaken by WALHI Sum-Sel and LBH Palembang, the third to analyzes the achievements of advocacy good experience. The method used is qualitative descriptive, with data retrieval purposively. Informants consisted of two NGO activists and community Rengas who know the specific background of the conflict. Technique of data collecting is done through in-depth interviews, observation, focus group discussion (FGD) conducted openly. The results showed that the conflict appears as a response to the process of industrialization Rengas society that go through PTPN VII Cinta Manis. There are three waves of peasant resistance Rengas namely, the first phase in 1981-1990 is not in the frontal, the second phase in 1991-2000 through the process of lobbying and litigation, the third phase is done through movement that is more sporadic and frontal. That conditions are different when the entry of NGO WALHI Sum-Sel and LBH Palembang in advocacy, there are four key strategies implemented strategies of persuasion, education, confrontation and litigation. Each strategy has been able to give positive effect in advocacy work. This marked the successful return of farmer Rengas manage an area of 1524 Ha. NGO advocacy work both have significant destinations for example, the development of local democracy, strengthening civil society and the response of policy makers. However the work done is not entirely smoothly. Advocacy work must still be run in order to maintain the sustainability movement. Valuable lessons can be learned from the advocacy of the importance of a comprehensive case analysis, strengthening of coalition, a massive campaign, as well as the actions of confrontation measured. All of it is important by social workers or job applicant advocacy.